KESALAHAN AFIKSASI DALAM TEKS CERITA FANTASI KELAS VII A SMP - Maharany, elva riezky; Wicaksono, Helmi; Yulianeta; Komariyah (Universitas Islam Malang, 2025)
Abstract: Language errors are a common phenomenon found in various written works. One type of error that often occurs is morphological errors, especially in the use of affixation. Mastery of affixation is an important part of Indonesian morphology which is still a common problem, this can be seen from the many errors in the use of affixation found in various writings. These errors can hinder the reader's understanding and reduce the quality of the written work. The purpose of this study is to describe, analyze, and correct the form of language errors in the use of affixation in fantasy story texts by students of grade VII A SMP Xin Zhong Surabaya. The method used is qualitative descriptive research using samples from seven fantasy story text works by students of grade VII A SMP Xin Zhong Surabaya. The stages carried out in data analysis are collecting fantasy story texts, selecting data by marking errors in the use of affixation, grouping errors in the use of affixation, presenting data analysis that has been grouped into the form of descriptions. The results of the study showed that errors in the use of Indonesian in fantasy story texts of students in grade VII A SMP Xin Zhong Kota Surabaya occurred in the misuse of affixation which included errors in writing prefixes (in- and ber-), suffixes (-pun, and nya), and confixes (peng-kan, per-an, and meng-kan).